Study of the in vivo role of Mce2R, the transcriptional regulator of mce2 operon in Mycobacterium tuberculosis - Forrellad, Marina Andrea; Bianco, María Veronica; Blanco, Federico Carlos; Nuñez, Javier; Klepp, Laura Ines; Vazquez, Cristina Lourdes; Santangelo, María De La Paz; Rocha, Rosana Valeria; Soria, Marcelo; Golby, Paul; Gutierrez, Maximiliano Gabriel; Bigi, Fabiana (BMC, 2019)
Background: Tuberculosis is one of the leading causes of mortality throughout the world. Mycobacterium tuberculosis, the agent of human tuberculosis, has developed strategies involving proteins and other compounds called virulence factors to subvert human host defences and damage and invade the human host. Among these virulence-related proteins are the Mce proteins, which are encoded in the mce1, mce2, mce3 and mce4 operons of M. tuberculosis. The expression of the mce2 operon is negatively regulated by the Mce2R transcriptional repressor. Here we evaluated the role of Mce2R during the infection of M. tuberculosis in mice and macrophages and defined the genes whose expression is in vitro regulated by this transcriptional repressor. Results: We used a specialized transduction method for generating a mce2R mutant of M. tuberculosis H37Rv. Although we found equivalent replication of the MtΔmce2R mutant and the wild type strains in mouse lungs, overexpression of Mce2R in the complemented strain (MtΔmce2RComp) significantly impaired its replication. During in vitro infection of macrophages, we observed a significantly increased association of the late endosomal marker LAMP-2 to MtΔmce2RComp-containing phagosomes as compared to MtΔmce2R and the wild type strains. Whole transcriptional analysis showed that Mce2R regulates mainly the expression of the mce2 operon, in the in vitro conditions studied. Conclusions; The findings of the current study indicate that Mce2R weakly represses the in vivo expression of the mce2 operon in the studied conditions and argue for a role of the proteins encoded in Mce2R regulon in the arrest of phagosome maturation induced by M. tuberculosis.